Onion seed vigor as affected by the hydric stress test - Piana, Zenório (1995)
An investigation was carried out to study the effectiveness of the hydric stress test on the evaluation of the onion (Allium cepa L.) seed vigor. Six lots of onion seeds, cultivar "Pira Ouro", were submitted to several tests such as germination, first count, cold test, accelerated aging, electrical conductivity, field emergence and hydric stress at 0, -3, -6 and -9 atm potentials. The experiments were conducted at the Seed Analysis Laboratory and at the Experimental Field of the Escola Superior de Agricultura "Luiz de Queiroz"-ESALQ/USP. The results suggested that the hydric stress test at -3 atm potential was highly correlated with the field emergence and with the cold test. This test can be indicated to evaluate the vigor of onion seeds.